2021
DOI: 10.1520/jte20200538
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial, Antioxidant, and Cytotoxicity Activities of CuO Nanopellets Synthesized by Surfactant-Free Hydrothermal Method

Abstract: Copper oxide nanopellets (CONPs) were produced by hydrothermal strategy. The particles were characterized by distinctive techniques. The synthesized particles were found to have pellet morphology with nonuniform thickness and varying sizes extending between 200 and 550 nm. Studies revealed their microbial nature against both Gram-positive and Gram-negative microscopic organisms, specifically Staphylococcus aureus, Bacillus subtilis, Pseudomonas fluorescens, and Escherichia coli and a plant parasitic pathogen F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Interestingly, recent literature do not present the complete picture of photocatalytic activity of metal NPs synthesized with the aid of plant extracts, and hence, this review paper tries to address the gaps, by providing insights into the development of novel NPs towards treatment of dye-contaminated wastewater with low price and high efficiency, via photocatalysis. employed for the preparation and stabilization of metallic NPs (Chen et al, 2001;Geethalakshmi and Sarada, 2012;Jamkhande et al, 2019, Krishna et al, 2016aPrashanth et al, 2016b;Krishna et al, 2017a;Krishna et al, 2017b;Sathyananda et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent literature do not present the complete picture of photocatalytic activity of metal NPs synthesized with the aid of plant extracts, and hence, this review paper tries to address the gaps, by providing insights into the development of novel NPs towards treatment of dye-contaminated wastewater with low price and high efficiency, via photocatalysis. employed for the preparation and stabilization of metallic NPs (Chen et al, 2001;Geethalakshmi and Sarada, 2012;Jamkhande et al, 2019, Krishna et al, 2016aPrashanth et al, 2016b;Krishna et al, 2017a;Krishna et al, 2017b;Sathyananda et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…ZO being a wide band gap semiconductor, it possesses a wide range of useful properties including electrical, chemical, optical and magnetic properties. Moreover, ZO can be applied in many evolving applications over gas sensing [12], catalysts [13], semiconductors [14], UV-shielding materials [15], nano generators [16], anticancer agents [17][18][19][20][21][22][23][24][25][26][27][28], antiviral and antibacterial agents [29][30][31]. Recent literatures revealed that undoped ZO and doped ZO find various interesting bioapplications .…”
Section: Introductionmentioning
confidence: 99%